Asymmetric sensitivity of ecosystem carbon and water processes in response to precipitation change in a semi‐arid steppe. (1st March 2017) - Zhang, Bingwei; Tan, Xingru; Wang, Shanshan; Chen, Minling; Chen, Shiping; Ren, Tingting; Xia, Jianyang; Bai, Yongfei; Huang, Jianhui; Han, Xingguo
Summary: Semi‐arid ecosystems play an important role in regulating the dynamics of the global terrestrial CO2 sink. These dynamics are mainly driven by increasing inter‐annual precipitation variability. However, how ecosystem carbon processes respond to changes in precipitation is not well understood, due to a lack of substantial experimental evidence that combines increased and decreased precipitation treatments. This study, a 3‐year field manipulation experiment with five precipitation levels conducted in a semi‐arid steppe, examined the impacts of increased and decreased precipitation on ecosystem CO2 (GEP: gross ecosystem photosynthesis; ER: ecosystem respiration; NEE: net ecosystem CO2 exchange), water exchange (ET: evapotranspiration), and resource use efficiency (CUE: carbon use efficiency; WUE: water use efficiency). We found that decreased precipitation reduced ecosystem CO2, water exchange and resource use efficiency significantly, while increased precipitation did not cause significant influence on them. That is, they responded more sensitively to decreased precipitation. Soil water availability was the most important driver determining changes in GEP, ER and ET. Changes in NEE, CUE and WUE were predominately regulated by soil temperature. Photosynthesis at leaf and ecosystem levels showed significantly greater sensitivity to changed precipitation than respiration and ET, and therefore determined the trends of net carbon uptake and resource use efficiency. This study highlighted an asymmetric response of ecosystem carbon and water processes to altered precipitation. This is potentially important for improving our understanding of how possible future changes in precipitation will affect the carbon cycle. Taking this asymmetric response into consideration will inevitably reduce uncertainties in predicting the dynamics of the global carbon cycle. A lay summary is available for this article. Abstract : Lay Summary